Pediatric ACEs and related life event screener (PEARLS) latent domains and child health in a safety-net primary care practice - Morgan Ye; Danielle Hessler; Derek Ford; Mindy Benson; Kadiatou Koita; Monica Bucci; Dayna Long; Nadine Burke Harris; Neeta Thakur (BMC, 2023)
Abstract Background Research examining the connections between individual adverse childhood experiences (ACEs) and how groupings of interrelated adversities are linked with subsequent health is scarce, limiting our understanding of risk during a period of rapid expansion of ACE screening in clinical practice. The study objective was to conduct a psychometric analysis to derive latent domains of ACEs and related life events and assess the association between each domain and health outcome. Methods Participants (3 months-11 years) were recruited from the University of California San Francisco Benioff's Children Hospital Oakland Primary Care Clinic. Children were screened with the Pediatric ACEs and Related Life Events Screener (PEARLS) (n = 340), which assessed 17 total ACEs and related life events, including forms of abuse, household challenges, and social risks. Domains were constructed using confirmatory factor analysis and associations between the three identified domains and 14 health outcomes were assessed using multivariable linear and logistic regression models. Results Three PEARLS domains were identified: Maltreatment (ω = 0.73, ɑ=0.87), Household Challenges (ω = 0.70, ɑ=0.82), and Social Context (ω = 0.55, ɑ=0.70). Measurement invariance was supported across both gender and screening format. All domains were associated with poorer general and behavioral health and stomachaches. Maltreatment and Social Context were additionally associated with eczema while only Social Context was associated with increased odds of reporting headaches and somatic symptoms. Conclusion In an underserved, urban west-coast pediatric population, the PEARLS found three adversity domains of Maltreatment, Household Challenges, and Social Context that all had an independent statistically significant association with poorer child health. The results provide a timely and more nuanced representation of risk that can inform clinical practice and policy using more targeted resources and interventions.